Duration of Maintained Hamstring Flexibility After a One-Time, Modified Hold-Relax Stretching Protocol - Spernoga, Scott G. (National Athletic Trainers' Association, Inc., 2001)
OBJECTIVE: Previous research suggests proprioceptive neuromuscular facilitation (PNF) stretching techniques produce greater increases in range of motion than passive, ballistic, or static stretching methods. The purpose of our study was to measure the duration of maintained hamstring flexibility after a 1-time, modified hold-relax stretching protocol. DESIGN AND SETTING: The study had a 1 × 1 mixed-model, repeated-measures design. The independent variables were group (control and experimental) and time (0, 2, 4, 6, 8, 16, and 32 minutes). The dependent variable was hamstring flexibility as measured in degrees of active knee extension with the hip flexed to 90°. Measurements were taken in a preparatory military academy athletic training room. SUBJECTS: Thirty male subjects (age, 18.8 ± 0.63 years; height, 185.2 ± 14.2 cm; weight, 106.8 ± 15.7 kg) with limited hamstring flexibility in the right lower extremity were randomly assigned to a control (no-stretch) group or an experimental (stretch) group. MEASUREMENTS: All subjects performed 6 warm-up active knee extensions, with the last repetition serving as the prestretch measurement. The experimental group received 5 modified (no-rotation) hold-relax stretches, whereas the control group rested quietly supine on a table for 5 minutes. Posttest measurements were recorded for both groups at 0, 2, 4, 6, 8, 16, and 32 minutes. RESULTS: The repeated-measures analysis of variance revealed a significant group-by-time interaction, a significant main effect for group, and a significant main effect for time. Dunnett post hoc analysis revealed a significant improvement in knee-extension range of motion in the experimental group that lasted 6 minutes after the stretching protocol ended. CONCLUSIONS: Our findings suggest that a sequence of 5 modified hold-relax stretches produced significantly increased hamstring flexibility that lasted 6 minutes after the stretching protocol ended.